SnapToReality: Aligning Augmented Reality to the Real World - Nuernberger, Benjamin; Ofek, Eyal; Benko, Hrvoje; Wilson, Andy (CHI '16 Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems, 2016)
Augmented Reality (AR) applications may require the precise alignment of virtual objects to the real world. We propose automatic alignment of virtual objects to physical constraints calculated from the real world in real time (“snapping to reality”). We demonstrate SnapToReality alignment techniques that allow users to position, rotate, and scale virtual content to dynamic, real world scenes. Our proof-of-concept prototype extracts 3D edge and planar surface constraints. We furthermore discuss the unique design challenges of snapping in AR, including the user’s limited field of view, noise in constraint extraction, issues with changing the view in AR, visualizing constraints, and more. We also report the results of a user study evaluating SnapToReality, confirming that aligning objects to the real world is significantly faster when assisted by snapping to dynamically extracted constraints. Perhaps more importantly, we also found that snapping in AR enables a fresh and expressive form of AR content creation.